Successful Penile Replantation and the Role of Postreplantation Sildenafil Therapy: Report of 2 Cases and Literature Review. Issue 3 (21st June 2019) - Fu, Shibo; Zheng, Dachao; Xie, Minkai; Yao, Haijun; Wang, Zhong
Abstract: Penile amputation is a rare clinical emergency necessitating urgent urologic and microsurgical intervention. Microvascular replantation has become a conventional form of management, associated with significantly increased viability of the implanted tissue and a lower rate of complications. However, postreplantation treatment intended to promote early recovery of sexual function has been reported only seldomly. Here we report 2 cases of successful penile replantation with postreplantation daily sildenafil therapy. The patients were followed for 24 months and 8 months, respectively, from the date of repair. First intercourse was achieved at 92 days and 105 days, respectively. This is the first report of the use of phosphodiesterase type 5 inhibitors in postoperative care of penile replantation.